Genomic Characterization and Distribution Pattern of a Novel Marine OM43 Phage - Yang, Mingyu; Xia, Qian; Du, Sen; Zhang, Zefeng; Qin, Fang; Zhao, Yanlin (Frontiers in Microbiology, 2021)
Bacteriophages have a significant impact on the structure and function of marine microbial communities. Phages of some major bacterial lineages have recently been shown to dominate the marine viral communities. However, phages that infect many important bacterial clades still remained unexplored. Members of the marine OM43 clade are methylotrophs with important roles in C1 metabolism. OM43 phages (phages that infect the OM43 bacteria) represent an understudied viral group with only one known isolate. In this study, we describe the genomic characterization and biogeography of an OM43 phage that infects the strain HTCC2181, designated MEP301. MEP301 has a genome size of 34,774 bp. We found that MEP301 is genetically distinct from other known phage isolates and only displays significant sequence similarity with some metagenomic viral genomes (MVGs). A total of 12 MEP301-type MVGs were identified from metagenomic datasets. Comparative genomic and phylogenetic analyses revealed that MEP301-type phages can be separated into two subgroups (subgroup I and subgroup II). We also performed a metagenomic recruitment analysis to determine the relative abundance of reads mapped to these MEP301-type phages, which suggested that subgroup I MEP301-type phages are present predominantly in the cold upper waters with lower salinity. Notably, subgroup II phages have an inverse different distribution pattern, implying that they may infect hosts from a distinct OM43 subcluster. Our study have expanded knowledge about the genomic diversity of marine OM43 phages and identified a new phage group that is widespread in the ocean.